Endogenous cell recruitment strategy for articular cartilage regeneration. (15th September 2020) - Yang, Zhen; Li, Hao; Yuan, Zhiguo; Fu, Liwei; Jiang, Shuangpeng; Gao, Cangjian; Wang, Fuxin; Zha, Kangkang; Tian, Guangzhao; Sun, Zhiqiang; Huang, Bo; Wei, Fu; et al.
Abstract: In the absence of timely and proper treatments, injuries to articular cartilage (AC) can lead to cartilage degeneration and ultimately result in osteoarthritis. Regenerative medicine and tissue engineering techniques are emerging as promising approaches for AC regeneration and repair. Although the use of cell-seeded scaffolds prior to implantation can regenerate and repair cartilage lesions to some extent, these approaches are still restricted by limited cell sources, excessive costs, risks of disease transmission and complex manufacturing practices. Recently developed acellular scaffold approaches that rely on the recruitment of endogenous cells to the injured sites avoid these drawbacks and offer great promise for in situ AC regeneration. Multiple endogenous stem/progenitor cells (ESPCs) are found in joint-resident niches and have the capability to migrate to sites of injury to participate in AC regeneration. However, the natural recruitment of ESPCs is insufficient, and the local microenvironment is hostile after injury. Hence, an endogenous cell recruitment strategy based on the combination of chemoattractants and acellular scaffolds to effectively and specifically recruit ESPCs and improve local microenvironment may provide new insights into in situ AC regeneration. This review provides a brief overview of: (1) the status of endogenous cell recruitment strategy; (2) the subpopulations, potential migration routes (PMRs) of joint-resident ESPCs and their immunomodulatory and reparative effects; (3) chemoattractants and their potential adverse effects; (4) scaffold-based drug delivery systems (SDDSs) that are utilized for in situ AC regeneration; and (5) the challenges and future perspectives of endogenous cell recruitment strategy for AC regeneration. Statement of Significance: Although the endogenous cell recruitment strategy for articular cartilage (AC) regeneration has been investigated for several decades, much work remains to be performed in this field. Future studies should have the following aims: (1) reporting the up-to-date progress in the endogenous cell recruitment strategies; (2) determining the subpopulations of ESPCs, the cellular and molecular mechanisms underlying the migration of these cells and their anti-inflammatory, immunomodulatory and reparative effects; (3) elucidating the chemoattractants that enhance ESPC recruitment and their potential adverse effects; and (4) developing advanced SDDSs for chemoattractant dispatch. Herein, we present a systematic overview of the aforementioned issues to provide a better understanding of endogenous cell recruitment strategies for AC regeneration and repair. Graphical abstract: Image, graphical abstract